2023
DOI: 10.1039/d2md00463a
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest binding of tetracationic cyclophanes to photodynamic agents inhibits posttreatment phototoxicity and maintains antitumour efficacy

Abstract: In the past two decades, photodynamic therapy (PDT) has become an effective method for the treatment of cancers. However, the posttreatment residue of photodynamic agents (PDAs) causes long-term skin phototoxicity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…To this end, Li et al. have recently developed a family of supramolecular organic frameworks [ 16 ] and naphthalene‐incorporated tetracationic cyclophanes [ 17 ] that can adsorb some clinically used photosensitizers, including Photofrin, HiPorfin, Talaporfin, and Chlorin e6 in the body of mice through host‐guest interactions. It has been found that the post‐treatment of these hosts can suppress the sunlight‐induced skin phototoxicity without affecting the PDT efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Li et al. have recently developed a family of supramolecular organic frameworks [ 16 ] and naphthalene‐incorporated tetracationic cyclophanes [ 17 ] that can adsorb some clinically used photosensitizers, including Photofrin, HiPorfin, Talaporfin, and Chlorin e6 in the body of mice through host‐guest interactions. It has been found that the post‐treatment of these hosts can suppress the sunlight‐induced skin phototoxicity without affecting the PDT efficacy.…”
Section: Introductionmentioning
confidence: 99%